Natural area tourism ecology, impacts and management - Dowling Ross K; Moore Susan; Newsome David (New Delhi Viva Books, 2006)
This text covers all the facets of tourism in natural areas. It is underpinned by a strong foundation of environmental understanding. It then describes the range of impacts, which occur when tourism takes place in the natural environment and illustrates
Keywords: Tourism